2008 8th IEEE International Conference on Automatic Face &Amp; Gesture Recognition 2008
DOI: 10.1109/afgr.2008.4813426
|View full text |Cite
|
Sign up to set email alerts
|

The looking back screens

Abstract: The Looking Back Screens demonstrator presents a high end 'multi-level' face analysis system that observes facial characteristics, expressions, gaze and (facial) gestures of viewers and integrates these viewer observations in various interactive 'games' with an infocus viewer .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Our research has highlighted the importance of incorporating naturalistic observations in training AFC models, addressing limitations associated with relying solely on standardised and controlled environments. Whilst FaceReader, a widely used AFC software ( Den Uyl and Van Kuilenburg, 2005 ; Noldus, 2014 ), has shown efficacy in specific conditions ( Höfling et al, 2021 ), challenges persist in accurately distinguishing between neutral and unpleasant stimuli and effectively handling non-standardised expressions ( Höfling et al, 2020 ; Küntzler et al, 2021 ). Nevertheless, AFC has demonstrated promise beyond academic research, particularly in predicting self-reported emotions and providing valuable insights in marketing research, where it captures non-verbal aspects ( Höfling and Alpers, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research has highlighted the importance of incorporating naturalistic observations in training AFC models, addressing limitations associated with relying solely on standardised and controlled environments. Whilst FaceReader, a widely used AFC software ( Den Uyl and Van Kuilenburg, 2005 ; Noldus, 2014 ), has shown efficacy in specific conditions ( Höfling et al, 2021 ), challenges persist in accurately distinguishing between neutral and unpleasant stimuli and effectively handling non-standardised expressions ( Höfling et al, 2020 ; Küntzler et al, 2021 ). Nevertheless, AFC has demonstrated promise beyond academic research, particularly in predicting self-reported emotions and providing valuable insights in marketing research, where it captures non-verbal aspects ( Höfling and Alpers, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The software has been validated and found to outperform human coders, correctly identifying 88% of expressions compared to 85% by humans ( Lewinski et al, 2014 ). FaceReader demonstrates high accuracy in classifying various expressions, with rates reported at 94% for Neutral, 82% for Scared, and other studies reporting performance rates ranging from 80 to 89% ( Den Uyl and Van Kuilenburg, 2005 ; Terzis et al, 2013 ; Skiendziel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This emotional expression is uniquely and reliably recognized in healthy controls with high specificity and sensitivity. Furthermore, given that the video analysis software recognizes happiness similarly to objective human observers with accuracy greater than 90%, its ability to detect happiness after face transplant at subclinical levels not perceptible to human observers highlights the potential of video analysis software as a rehabilitative tool.…”
Section: Discussionmentioning
confidence: 99%